PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP PEMBENTUKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) KARYAWAN DALAM RANGKA PENINGKATAN KINERJA - M. Saleh Lubis (Jurnal Apresiasi Ekonomi, 2015)
This research was conducted to investigate the influence of organizational climate and organizational commitment on organizational citizenship behavior (OCB) in order to improve employee performance. The object of research is the employee of STIE Pasaman Simpang Empat. The research conducted by the kausalistik relationships method. The test results showed that the organizational climate significant effect on OCB, organizational commitment significant effect on OCB, organizational climate significant impact on performance, organizational commitment significant effect on the performance and OCB significant impact on performance. The results of this study imply that the leader of STIE Pasaman Simpang Empat in improving employee performance through increased OCB should begin with efforts to improve the organizational climate and organizational commitment. Keywords: Performance, organizational citizenship behavior (OCB), organizational climate and organizational commitment.